Hubungan Riwayat Konsumsi Minuman Beralkohol Dengan Kejadian Gout Arthritis Di Rumah Sakit Daerah Langowan - Seko, Rivaldo V; Malara, Reginus T; Nurmansyah, Muhamad (Mapalus Nursing Science Journal, 2023)
Abstract Background : Gout arthritis is an arrthritis due to hoarding crystal uric acid which can be affected by various factors, on of them is consumption od alcoholic drinks. Aim : Determine the relationship between alcoholic beverage consumption and gout arthritisl. Methods: Observational with Case control design. The samples of this study is 162 patients case and 162 patients control using purposive sampling. The research is using patients’ medical records from 2016-2020. Data analysis is using chi-square method. Result: According to statistical test it is there is a relation between historic alcoholic beverage consumption with the occurences of gout arthritis concluded that Odds Ratio : 8,56 with p value =0,000. Discussion: Factors that influence the occurrence of gout arthritis in the hospital is a history of high consumption of alcoholic beverages because its contain purines. Conclusion: there were 139 patients (85,8%) diagnosed with gout arthritis who had a history of consuming alcoholic beverages, while 67 patients in the control group were not diagnosed with gout arthritis. patients with a history of consuming alcoholic beverages are at risk of 8.56 times to experience gout arthritis compared to patiens who do not have a history of consuming alcoholic beverages at Budi Setia Langowan Hospital. Suggestion fortim medic. Can provide education to society about the impact or consequences that consume alcoholic beverages Keywords: Adults, Alcoholic Beverage Consumption, Gout Arthritis